PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). Demichow W. Die experimentelle Transplantation lebenswichtiger Organe. Berlin: VEB Verlag Volk und Gesundheit, 1963 - S. P. Glyantsev; A. Werner (Трансплантология (Москва), 2020)
The article has discussed V.P. Demikhov's views on a homoplastic transplantation of tissues and organs in 1963 and his achievements in experimental transplantation by that time. The authors first translated the monograph Die experimentelle Transplantation lebenswichtiger Organe (1963) from German into Russian and presented V.P. Demikhov's Preface to it. In this text, having critically analyzed the current provisions in the field of immunobiology, V.P. Demikhov came to the conclusion that a number of his achievements contradicted those provisions and did not fit into the framework of existing immunobiological laws. In 1963, confessing the primacy of function over structure, V.P. Demikhov believed that the restoration of blood circulation in transplanted organs played the main role in their survival, and the subsequent functioning of the transplanted organ for a long time meant its engraftment. In this text V.P. Demikhov for the first time substantiated the model of a “physiological organism” he had invented for reviving a human in a state of agony, for creating a bank of organs, growing it in infants and rejuvenating the elderly.Authors declare no conflict of interest.